الوصية كتصرف ناقل للملكية العقارية - فرطاس, أحمـــد; عرجون, خالد (University of Eloued جامعة الوادي, 2023)
تصرَف الوصية بالعقارات في أملاك العقارات التابعة للتركة، بما يزيد على حصة الميراث الشرعية، وتعد وفاءً بإرادة فردية من الموصي، وللموصي بالحق أن يتراجع عن الوصية أو يعدِّلها في أي وقت أثناء حياته. تقوم الوصية بالعقارات على أركان تشمل الصيغة والموصي والموصى له والموصى به، بالإضافة إلى الشروط الشكلية الرسمية. وفي هذه الحالة، يتعين أن تلتزم الوصية بإجراءات العقود الناقلة للملكية العقارية، ويجب توثيقها عند الضابط العمومي وتسجيلها في المحافظة العقارية لضمان استحقاق الحقوق المالية المرتبطة بها. بعد وفاة الموصي، تنتقل الملكية العقارية من خلال قبول الموصى بها من قبل الموصى له، ويتم ذلك في حدود ثلث التركة، مع الحصول على إجازة الورثة في حالة تجاوز الثلث. وفي حالة عدم منح الإجازة، تقتصر الوصية على الثلث، أو يُعاد الملكية العقارية بأكملها إلى التركة إذا كان الموصى به هو وريثٌ للترك The will is disposed of in real estate in the estate belonging to the estate, in excess of the share of the legal inheritance, and is considered to fulfill the individual will of the testator, and the trustee has the right to withdraw or amend the will at any time during his life. The will carries real estate on pillars that include formula, testator, recommended and recommended, in addition to the formal formal conditions. In this case, the will must abide by the procedures of contracts transferring real estate ownership, and it must be documented with the public officer and registered in the real estate governorate to ensure that the associated financial rights are due. After the testator’s death, the real estate is transferred by accepting the recommended by the recommended, and this is done within one third of the estate, with the heirs ’leave being obtained in the event of exceeding one third. In the event that the leave is not granted, the will is limited to one third, or the entire real estate is returned to the estate if the recommended is the heir to the estate.
مذكرة ماستر
Keywords: الوصية , العقارية , الملكية; will , real estate , Property .